PENGARUH MODEL PEMBELAJARAN PICTURE AND PICTURE TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS II SDN 01 PADANG LAWEH - Dodi Widia Nanda; Aprimadedi; Isnaryati (STKIP Subang, 2023)
Education is very important in human life at all times. Or it is called lifelong education, because education has a role in improving the quality of Indonesian people as a whole. The problem that forms the background of this study is the low learning outcomes of class II students at SDN 1 Padang Laweh in mathematics content in learning theme 4 sub-themes 2. In an effort to overcome this problem it is necessary to apply the picture and picture learning model to mathematics content. This study uses the type of Pre-Experimental design One-Group Pretest-Posttest Design. The population and sample are all 15 students in grade II SDN 1 Padang Laweh. The results of data collection techniques were taken using pretest and posttest sheets calculated and compared based on criteria and analyzed by normality tests and hypothesis tests through SPSS 20 at a level of 0.05. While the test data collection technique was taken using a test sheet and then also analyzed using the normality test and hypothesis testing through SPSS 20 at a level of 0.05. The results of data analysis from hypothesis testing on paired sample tests with a significance level of 0.05 show the results of sig. (2-tailed) is smaller than a or in the equation 0.000 <0.05, then H0 is rejected. While the results of the analysis of the test data from the hypothesis test on the paired sample test with a significance level of 0.05 showed the results of sig. (2-tailed) is smaller than a or in the equation 0.000 <0.05, then H0 is rejected. Based on the results of the analysis of observation data and test data, it can be concluded that the picture and picture model has a significant influence on student learning outcomes in class II elementary school mathematics content